The Arabidopsis thaliana trp5 mutant has a feedback-resistant anthranilate synthase and elevated soluble tryptophan. - Li, J (1996)
The first step of tryptophan biosynthesis is catalyzed by anthranilate synthase (AS), which is normally subject to feedback inhibition by tryptophan. Three independent trp5 mutants defective in the Arabidopsis thaliana AS alpha subunit structural gene ASA1 were identified by selection for resistance to the herbicidal compound 6-methylanthranilate. In all three mutants these biochemical changes are caused by a single amino acid substitution from aspartate to asparagine at residue position 341. Compared with the enzyme from wild-type plants, the tryptophan concentration causing 50% inhibition of AS activity in the trp5 mutant increased nearly 3-fold, the apparent Km for chorismate decreased by approximately 50%, and the apparent Vmax increased 60%. As a consequence of altered AS kinetic properties, the trp5 mutants accumulated 3-fold higher soluble tryptophan than wild-type plants. However, even though the soluble tryptophan levels were increased in trp5 plants, the concentrations of five tryptophan biosynthetic proteins remained unchanged. These data are consistent with the hypothesis that the reaction catalyzed by A. thaliana AS is rate limiting for the tryptophan pathway and that accumulation of tryptophan biosynthetic enzymes is not repressed by a 3-fold excess of end product.